Pos Malaysia: the study of PosLaju / Nurul Fatihah Mohd Karim, Nur Irdina Mohd Nasri and Suley Norsyakila Yahya - Mohd Karim, Nurul Fatihah; Mohd Nasri, Nur Irdina; Yahya, Suley Norsyakila (2019)
Pos Malaysia Berhad has four main business units, which are PosMel, PosNiaga, PosLaju and PosLogistic. This four business unit has its own responsibilities. PosMel provides the service for mail and parcel normal delivery in Malaysia or outside the nation. PosNiaga handles the operations of business to thrive and grow with the proper systems and solutions. Meanwhile, PosLaju handles express delivery for mails or parcels either domestic or international. PosLogistic is the services that handles the operations of logistic for air, land and water transportation in order to deliver the mail or parcel to or from its customers. One of the most frequently used services is delivery service by PosLaju. Thus, the study is focusing on PosLaju.